Preoperative chemoradiation with paclitaxel-carboplatin or with fluorouracil-oxaliplatin—folinic acid (FOLFOX) for resectable esophageal and junctional cancer: the PROTECT-1402, randomized phase 2 trial. Issue 1 (December 2016) - Messager, Mathieu; Mirabel, Xavier; Tresch, Emmanuelle; Paumier, Amaury; Vendrely, Véronique; Dahan, Laetitia; Glehen, Olivier; Vasseur, Frederique; Lacornerie, Thomas; Piessen, Guillaume; El Hajbi, Farid; Robb, William; et al.
Abstract Background Often curative treatment for locally advanced resectable esophageal or gastro-esophageal junctional cancer consists of concurrent neoadjuvant radiotherapy and chemotherapy followed by surgery. Currently, one of the most commonly used chemotherapy regimens in this setting is a combination of a fluoropyrimidin and of a platinum analogue. Due to the promising results of the recent CROSS trial, another regimen combining paclitaxel and carboplatin is also widely used by European and American centers. No clinical study has shown the superiority of one treatment over the other. The objective of this Phase II study is to clarify clinical practice by comparing these two chemotherapy treatments. Our aim is to evaluate, in operable esophageal and gastro-esophageal junctional cancer, the complete resection rate and severe postoperative morbidity rate associated with these two neoadjuvant chemotherapeutic regimens (carboplatin-paclitaxel or fluorouracil-oxaliplatin-folinic acid) when each is combined with the radiation regime utilized in the CROSS trial. Methods/design PROTECT is a prospective, randomized, multicenter, open arms, phase II trial. Eligible patients will have a histologically confirmed adenocarcinoma or squamous cell carcinoma and be treated with neoadjuvant radiochemotherapy followed by surgery for stage IIB or stage III resectable esophageal cancer. A total of 106 patients will be randomized to receive either 3 cycles of FOLFOX combined to concurrent radiotherapy (41.4 Grays) or carboplatin and paclitaxel with the same radiation regimen, using a 1:1 allocation ratio. Discussion This ongoing trial offers the unique opportunity to compare two standards of chemotherapy delivered with a common regimen of preoperative radiation, in the setting of operable locally advanced esophageal or gastro-esophageal junctional tumors. Trial registration NCT02359968 (ClinicalTrials.gov) (registration date: 9 FEB 2015), EudraCT: 2014-000649-62 (registration date: 10 FEB 2014)